Pengaruh Kepemimpinan Digital Terhadap Kinerja Tim Virtual - Armadin Armadin; Sunarto Sunarto (Green Publisher Indonesia, 2026)
This reserch aims to analyze the influence of digital leadership on virtual team performance in the context of modern organizations that increasingly rely on information and communication technology. The development of digitalization has driven a shift in work patterns from conventional to virtual, requiring leaders to possess adaptive skills in managing remote teams. This study used a descriptive qualitative approach with a literature review method, which examined various theories and previous research findings related to digital leadership and virtual team performance. The study focused on leaders' ability to utilize technology, build effective communication, enhance team collaboration, and foster trust in a virtual work environment. The results indicate that digital leadership has a significant influence on improving virtual team performance. Leaders who are able to integrate technology with a communicative, responsive, and collaborative leadership style can increase productivity, engagement, and teamwork effectiveness. Conversely, a lack of digital and communication skills can hinder coordination and decrease team performance. Therefore, it can be concluded that digital leadership is a critical factor in supporting the success of virtual teams. Therefore, organizations need to develop the digital competencies of leaders to effectively manage teams in the digital era.